Insomnia, pruritus, and constipation in hemodialysis patients: a cross-sectional study - Zhu, Jing; Wang, Bifei (Frontiers in Physiology, 2025)
BackgroundInsomnia, pruritus, and constipation are among the most prevalent chronic symptoms in hemodialysis patients, significantly impairing their quality of life. However, their risk factors and interrelationships are unclear. This study aimed to investigate the potential interrelationships among insomnia, pruritus, and constipation, as well as their associations with clinical and laboratory parameters in patients undergoing maintenance hemodialysis.MethodsSleep quality was evaluated using the Athens Insomnia Scale, while pruritus was assessed based on patient-reported occurrences in the past 4 weeks. Constipation was diagnosed according to the Rome IV criteria for functional gastrointestinal disorders. Additional clinical and laboratory parameters were collected for comprehensive analysis. Statistical analyses included the t-test, Mann-Whitney U test, chi-square test, multivariate logistic regression,and receiver operating characteristic curve.ResultsA total of 210 patients were included in this study. Insomnia was reported in 114 patients (54.3%), pruritus in 86 (41.0%), and constipation in 36 (17.1%). Patients with insomnia exhibited significantly higher serum calcium levels than those with normal sleep (P = 0.029). Insomnia was more prevalent among patients with pruritus (P = 0.009) and constipation (P = 0.006). Binary logistic regression identified elevated calcium levels (P = 0.045; OR = 3.613), pruritus (P = 0.014; OR = 2.078), and constipation (P = 0.012; OR = 2.882) as independent risk factors for insomnia. Hemodialysis patients with pruritus presented with elevated pre-dialysis creatinine (P = 0.002), post-dialysis creatinine (P = 0.012), post-dialysis urea levels (P = 0.035), creatinine clearance during dialysis (P = 0.001), ultrafiltration (P = 0.013), and ultrafiltration rate (P = 0.008) compared to those without pruritus. Insomnia (OR = 2.012, P = 0.019) and creatinine clearance during dialysis (OR = 1.002, P = 0.018) were identified as independent risk factors for patients with pruritus. Constipated patients exhibited significantly lower dialysis urea clearance than non-constipated patients (P = 0.005). Dry weight was higher in the constipated group (P = 0.024), and the prevalence of insomnia was significantly elevated compared to non-constipated patients (P = 0.006). Binary logistic regression analysis identified insomnia as an independent risk factor for constipation (P = 0.006; OR 3.253). Conversely, higher urea clearance during dialysis served as a protective factor against constipation (P = 0.013; OR 0.883). ROC curve analyses revealed AUC values of 0.59 for serum calcium in diagnosing insomnia, 0.64 for creatinine clearance during dialysis in diagnosing pruritus, and 0.65 for urea clearance during dialysis in diagnosing constipation.ConclusionInsomnia, pruritus, and constipation demonstrate both complex interrelationships and independent effects, collectively contributing to substantial quality-of-life impairment in maintenance hemodialysis patients.